EVALUATION OF CYTOLOGICAL VARIATIONS IN HYDROXYLAMINE HYDROCHLORIDE AND X-RAY-INDUCED M1 AND M2 GENERATIONS OF GROUNDNUT (Arachis hypogea L.) GENOTYPES - Abubakar; Musa; Kutawa; Yakubu; Banani; Mubarak; Sani (FUDMA Journal of Sciences, 2026)
It is pertinent to concede the transmissible portion of polymorphism as it provides heterogeneity component measure for the transmission of traits to next generation. The research is aim at evaluating cytological variations in Hydroxylamine hydrochloride and X-ray-induced M1 and M2 generations of groundnut (Arachis hypogea L.) genotypes. Groundnut production in Nigeria is constrained by multiple factors including low genetic variability. Pot trials were carried out during 2024/2025 dry seasons at the teaching and research field, Department of Plant Science and Biotechnology, Bayero University, Kano. Two improved groundnut genotypes (SAMNUT-24, SAMNUT-25) were collected from Kano State Agricultural and Rural Development Authority (KNARDA) and the two Local varieties (’YAR-GINGO and ’YAR-FARA) were collected from Dawanau Market, Dawakin Tofa Local Government Kano State. The experimental design used was Complete Randomized Design (CRD) with a total of nine hundred seeds of each variety. The seeds were soaked in different concentrations of Hydroxylamine hydrochloride (0.00mM, 1.0mM, 2.0mM, 3.0mM and 4.0mM) for three (3) hours. Seed irradiation was carried out at Radiography department, Specialist Hospital Dutsin-Ma, Katsina State at 0, 100, 200, 300 and 400 Gy, with non-irradiated bag as the control. The results revealed significant variation among the genotypes. YARGINZO treated with maximal dose of Hydroxylamine Hydrochloride at 3.0 Mm and SAMNUT-25 at 4.0mM produced highest frequency of severely aneuploidy cells when compared to control and the remaining treatments. It is recommended that, farmers should adopt the use of genotypes with mild hyper-aneuploidy and near-aneuploidy best for genetic improvement due to relative stability.